Application of Calibration Curve, Accuracy and Precision Chart as Internal Quality Control at COD Testing in Wastewater - Lusiana, Uray (Biopropal Industri, 2012)
Quality assurance is one of the technical requirements that include in the quality management system based on SNI ISO/IEC 17025 : 2008. Quality assurance is all the process that planned and systematic activity that applied in analysis, so can give the confidence to the customer or data user. Quality assurance that is applied for COD testing in wastewater are calibration curve, accuracy and precision control chart. The purpose of calibration curve, accuracy and precision control chart applied was to control the data of COD testing so that guaranty the validity to report and to keep the consistence of testing result as statistic all the time. Calibration curve of COD testing have a coefficient correlation 0,99987. Accuracy control chart have limited line BTA = 104,95%, BPA = 102,97%, BIA = 100,98%, BTB = 93,03%, BPB = 95,02% and BIB = 97,0%. Accuracy data can be accepted if that data present between line of BPA and BPB (± 2 SD), data is warned if that data present between line BTA-BPA or BTB-BPB (± 2 SD and ± 3 SD), and data is outlier if that data present out of line BTA and BTB (± 3 SD). The precision data can accepted if that the RPD value is not more than 10 % of COD testing result.